T-Box Transcription Factor 22 Is an Immune Microenvironment-Related Biomarker Associated With the BRAFV600E Mutation in Papillary Thyroid Carcinoma - Dong, Xubin; Song, Jingjing; Hu, Jing; Zheng, Cheng; Zhang, Xiaohua; Liu, Haiguang (Frontiers in Cell and Developmental Biology, 2020)
Papillary thyroid cancer (PTC) is the most common malignant disease in endocrine systems. T-box transcription factor 22 (TBX22) is a phylogenetically conserved family member that has not been widely characterized in cancers. In this study, we explored the potential clinical significance and biological functions of TBX22 in PTC. Comprehensive analyses of TBX22 were based on the public databases and our local qRT-PCR cohort. We observed that TBX22 was signiﬁcantly down-regulated in PTC compared with normal tissues. TBX22 was associated with several clinicopathological factors in PTC. Low TBX22 expression correlated with BRAFV600E and TERT mutation. Functional enrichment analysis revealed that cancer-related pathways and immune progress were closely associated with TBX22 in PTC. In TBX22-low PTC, high immune inﬁltration levels with increased CD8+ T-cells, natural killer, M1 macrophages, and T-regulatory cells were observed. TBX22 was negatively correlated with the activity of different steps of the anti-cancer immunity cycle. Functionally, overexpression of TBX22 inhibited proliferation, invasion, and migration in PTC cells, while knocking down of TBX22 showed the opposite effects. The present findings disclose that TBX22, as an immune microenvironment-related biomarker, could be an important tumor suppresser gene and might inform the management of PTC patients better.